Lokakarya Pemanfaatan Media Film Melalui Sosialisasi Pengelolaan Sampah Berdasarkan Konsep Kewarganegaraan Ekologis Sebagai Upaya Meningkatkan Karakter Peduli Lingkungan - Esty Rahmayanti; Dedi Eko Nur Cahyo; Nur Rahmat Ardi Candra (Jurnal Pengabdian Kampus, 2025)
Film is an effective medium for raising environmental awareness due to its visual appeal and ability to convey messages in an engaging manner. Films are not only entertaining but also convey ideologies that can influence audience attitudes and behavior, including fostering environmental stewardship. Waste management remains a serious issue in Indonesia, including in Longkeyang Village, Pemalang. Lack of public awareness of the importance of environmental protection is evident in the habit of littering, burning, and the lack of facilities such as landfills (TPA), waste disposal sites (TPST), or waste banks. Low levels of education and the lack of supporting media exacerbate this situation. Recognizing this urgency, this Community Service Program (PKM) activity aims to increase the understanding and awareness of Longkeyang Village residents regarding waste management based on the concept of ecological citizenship. This concept emphasizes citizens' responsibility in protecting the environment as part of national character and morals. Through a creative and communicative educational approach, this PKM activity utilizes the short film "Pulau Plastik," a documentary, as a socialization tool. By leveraging the power of cinema as an educational medium, this activity can empower the community through an applied artistic approach. Keywords: film; waste management; ecological citizenship; environmental care character